Severity of cystocele and risk factors of postoperative stress urinary incontinence after laparoscopic sacrocolpopexy for pelvic organ prolapse - Hirotaka Sato; Hirokazu Abe; Atsushi Ikeda; Tomoaki Miyagawa; Sachiyuki Tsukada (Wolters Kluwer Medknow Publications, 2022)
Objectives: Knowledge on the severity of cystocele and incidence of postoperative stress urinary incontinence (SUI) after prolapse repair is lacking. This study investigated the incidence and risk factors of postoperative SUI following laparoscopic sacrocolpopexy (LSC). Materials and Methods: We retrospectively reviewed the charts of 83 women without occult SUI who underwent LSC for pelvic organ prolapse and developed SUI over 3 months postoperatively. We used Fisher's exact test, the Mann-Whitney U-test, and logistic regression for statistical data analyses. Results: After 3 months, the incidences of postoperative SUI were 50% and 24% in those who did and did not report preoperative SUI, respectively. Eventually, postoperative SUI was reported by 39% and 9% of the women with and without preoperative SUI, respectively. Increased Ba (point of maximal anterior vaginal wall prolapse) measurement (odds ratio [OR], 1.44; 95% confidence interval [CI], 1.0-2.06; P = 0.04) and preoperative SUI (OR, 3.95; 95% CI, 1.14-13.7; P = 0.03) were the risk factors for postoperative SUI. Conclusion: Our findings suggest that counseling regarding the risk of postoperative SUI should be conducted for women with preoperative advanced cystocele or bothersome SUI.